Black Markets: Beckett's Bad Equilibrium. Issue 1 (April 2018) - Walker, Dominic
Abstract : Much as Murphy (1938) insists that desire is a 'closed system' in which 'the quantum of wantum does not vary', the Knott household in Watt (1953) seems to be a closed system 'to which nothing could be added' and from which 'nothing could be taken away' (Mu, 38–9, Wa, 111). Yet the random variable of Knott's appetite produces an instability that must be corrected to maintain equilibrium. This essay argues that Watt's efforts to dispose of Knott's leftover food work through a problem of equilibrium with consequences for Beckett's ideal of compositional practice. In October 1932, Beckett says to Thomas MacGreevy that writing should be a 'spontaneous combustion of the spirit to compensate the pus & pain that threatens its economy' (LSB 1, 134–5). The 'poem', he adds in September 1935, must be 'useful in the depths, where demand and supply coincide, and the prayer is god' (LSB 1, 274). Using two variant passages from Watt and Molloy, I will suggest that Beckett's growing scepticism about this economic conception of imaginative work was partly due to some unhappy historical parallels concerning the discourse of equilibrium. The first variant passage I consider is the coprophagic economy of Ballyba, administered by a bureaucratic organisation called 'Organisation Maraîchère' ('Market Garden Organisation'). Having identified an overlooked deictic marker concerning a misbegotten WW2 mission and an unfortunate cryptonym, the essay argues that Ballyba's insistence on eliminating waste was too historically suggestive to be included in the published text. The second variant passage is an 8300-word continuation of the problem of Mr Knott's dinner, ending in a notorious 'spectacle' of canine love, put on by the Lynch family for the amelioration of the local population (Beckett, 1945, 297). I argue that this final, orgiastic solution to the problem of Mr Knott's dinner spells out the philosophical consequences of trying to eliminate waste and ensure supply and demand 'coincide'. The essay concludes there were good historical reasons for Beckett to turn away from his credo of 'personal and aesthetic equilibrium', as Mark Nixon puts it, and towards a more commodious art of 'mess' and 'pre-established arbitrary' (Nixon 2011, 37, Wa, 114). The most wastefully written vignette in Watt (1957) [1945] is about eliminating the waste from Mr Knott's dinner. This is a job, we are ominously reassured, that 'gave very little trouble' (Beckett, 2009d, 72). In the published text, Knott's waste-disposal problem goes on for 30 pages, as Watt attempts to rig up an economy to off-set the unpredictability of his employer's appetite, the vagaries of the human and canine lifespans, and so on. Underlying this insistence on the elimination of waste is the principle of equilibrium. This is made more exhaustively clear in the 1945 typescript, where Watt pursues the errant leftovers to their endpoint some 8, 300 words later: a notorious 'spectacle' of canine love, put on by the Lynch family for the amelioration of the local population, in which one dog is left out of the fun (Beckett, 1945, 297). Equilibrium was Beckett's model for aesthetic 'spontane[ity]' in the 1930s, but Watt's obscene meditation on the imperative to eliminate waste shows him having misgivings about it (Beckett, 2009a, 134). Using another variant passage from the Molloy notebooks, this essay argues that Beckett is drawn to economics as a way of working through the historically troubling implications of an aesthetic philosophy he had already found wanting. It will suggest that the Ballyba passage, which describes an economy where human beings are principally regarded as shit, was omitted from the published text of Molloy (1951) because its many inadvertent parallels with totalitarian bureaucracies throw out a delicate comic economy. It will point to one overlooked example of the novel's scant deictic markers to show how that economy works. It will conclude that, although there is no intrinsic link between the kind of economics Beckett uses in his comedy and his use of economics as a way of working through aesthetic problems, his jettisoned black markets are a painstaking indictment of the economic model, based on equilibrium, that subtends them both.